Development of a Microlearning-based e-Module to Improve Seventh-Grade Students' Understanding of Triangle and Quadrilateral - Marpaung, Cichi Farhan Syahmar; Priatna, Nanang; Suhendra, Suhendra (Jurnal Pendidikan MIPA, 2024)
Understanding concepts in learning mathematics, especially triangles and quadrilaterals, is crucial. However, students often struggle with this material due to invalid and impractical teaching resources. This research aimed to develop valid and practical microlearning-based e-modules using a 3-D research model to improve students' understanding of triangles and quadrilaterals. Conducted at a junior high school in Sei Suka, Batu Bara Regency, North Sumatra Province, data were collected through interviews and questionnaires, utilizing instruments such as interview guides, expert validation sheets, and practicality test questionnaires. Data analysis included qualitative methods to reduce interview data and quantitative likert scale calculations. The developed e-modules were rated very valid by media and material experts and very practical by teachers. Testing on students showed that e-modules were quite practical on a small scale and very practical on a large scale. The effectiveness test revealed a significant improvement in students' understanding, with a gain score of 0.79, categorized as high. These results confirm that the microlearning-based e-module is valid, practical, and effective in enhancing students' understanding of triangles and quadrilaterals.        Keywords: E-modul, microlearning, triangle and quadrilateral. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1244-1258